Microbial phylogenetic relatedness links to distinct successional patterns of bacterial and fungal communities. (2nd March 2022) - Lin, Qiang; Dini‐Andreote, Francisco; Meador, Travis B.; Angel, Roey; Meszárošová, Lenka; Heděnec, Petr; Li, Lingjuan; Baldrian, Petr; Frouz, Jan
Summary: The mechanisms underlying microbial community dynamics and co‐occurrence patterns along ecological succession are crucial for understanding ecosystem recovery but remain largely unexplored. Here, we investigated community dynamics and taxa co‐occurrence patterns in bacterial and fungal communities across a well‐established chronosequence of post‐mining lands spanning 54 years of recovery. Bacterial community structures became increasingly phylogenetically clustered with soil age at early successional stages and varied less at later successional stages. The dynamics of bacterial community phylogenetic structures were determined by the changes in the soil vegetation cover along succession. The dynamics of fungal community phylogenetic structures did not significantly correlate with soil age, soil properties or vegetation cover, and were mainly attributed to stochastic processes. Along succession, the common decrease in the bacterial co‐occurrence complexity and in the average pairwise phylogenetic distances between co‐occurring bacteria implied a decrease in potential bacterial cooperation. The increased complexity of fungal co‐occurrence along succession was independent of phylogenetic relatedness between co‐occurring fungi. This study provides new sights into ecological mechanisms underlying bacterial and fungal community succession.